Maya and Arnold: Exterior Lighting and Rendering. - Maestri, George (linkedin.com, 2020)
Learn Arnold rendering in Maya for architectural exteriors. Instructor George Maestri shows how to set up, light, render, and composite shots for daytime and nighttime.